The Impact of Entrepreneurship Education and Business Incubators to Entrepreneurial Intention in President University - Felix Goenadhi; Dewi Gayatri (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
This study investigates the influence of entrepreneurship education and business incubators on the entrepreneurial intentions of first-year students at President University. Amidst fluctuating economic conditions and declining job market demands, understanding the factors that encourage entrepreneurship becomes crucial for reducing unemployment and enhancing economic productivity. Utilizing a quantitative research method, an online survey was administered to 125 students to assess their socio-demographic profiles, participation in entrepreneurship programs, and their intentions to become entrepreneurs. The analysis reveals a significant positive correlation between entrepreneurship education and entrepreneurial intentions, with students expressing high motivation to start their own businesses following participation in the Economic Survival courses. Additionally, the presence of the SetSail BizAccel business incubator further bolstered these intentions by providing necessary resources and mentorship. The findings underscore the importance of integrated educational frameworks that combine theoretical knowledge with practical support, emphasizing the role of entrepreneurship in fostering economic sustainability, innovation, and personal development among students. These insights are essential for policymakers and educational institutions aiming to cultivate a vibrant entrepreneurial ecosystem in Indonesia.